2017
DOI: 10.1002/mc.22668
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 2 drives tumorigenesis in human prostate cells in a mechanism involving androgen receptor and p53‐p21 axis

Abstract: Glyoxalase 2 (Glo2), a metabolic enzyme, is overexpressed in some human cancers which suggests this enzyme may play a role in human tumorigenesis. In prostate cancer (PCa), the role of Glo2 has been scarcely investigated and there are no studies addressing a causative involvement of this protein in this neoplasia. Here, we examined the immunohistochemical profile of Glo2 in human PCa and benign adjacent tissues and investigated Glo2 involvement in PCa development in human prostate cell lines. PCa and matched a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 59 publications
3
40
0
Order By: Relevance
“…Methylglyoxal is metabolized mainly by glyoxalases [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ], with minor metabolism by aldoketo reductases (AKRs) and aldehyde dehydrogenases (ADHs) [ 19 , 40 , 78 , 79 , 80 , 81 ] that convert it to hydroxyacetone and pyruvate, respectively [ 82 ]. Glyoxalases are cellular enzymes whose increased expression and activity in tumor tissues and/or cell lines [ 77 , 83 , 84 , 85 ], including those from the urogenital tract [ 86 , 87 , 88 , 89 , 90 ], have been widely documented [ 77 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In the present review, we provide an overview of the role of glyoxalases in the onset and progression of human urogenital malignancies and glyoxalases’ potential as targets for anticancer drug development and biomarkers for diagnosis or prognosis of urological cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Methylglyoxal is metabolized mainly by glyoxalases [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ], with minor metabolism by aldoketo reductases (AKRs) and aldehyde dehydrogenases (ADHs) [ 19 , 40 , 78 , 79 , 80 , 81 ] that convert it to hydroxyacetone and pyruvate, respectively [ 82 ]. Glyoxalases are cellular enzymes whose increased expression and activity in tumor tissues and/or cell lines [ 77 , 83 , 84 , 85 ], including those from the urogenital tract [ 86 , 87 , 88 , 89 , 90 ], have been widely documented [ 77 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In the present review, we provide an overview of the role of glyoxalases in the onset and progression of human urogenital malignancies and glyoxalases’ potential as targets for anticancer drug development and biomarkers for diagnosis or prognosis of urological cancers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scanty number of PCa samples considered in those studies significantly limited a reliable interpretation on the biological significance of Glo2 in this neoplasia. Only recently we causatively demonstrated a role of Glo2 in this neoplasia [36,37] providing in vivo and, in vitro, evidence for a role of this enzyme in prostate carcinogenesis. In particular, we showed that Glo2 was selectively expressed in PCa but not in the luminal compartment of the adjacent benign epithelium consistently in all the examined cases (n = 20).…”
Section: Glo2mentioning
confidence: 94%
“…Notably, a distinctly high activity of Glo1 was observed in 22 out of 22 PCa specimens and none to little activity in 10 out of 10 non-malignant specimens. Although preliminary, these results opened new pathways of investigation towards the study of Glo1 expression, either at mRNA, protein or functional level, in PCa tissues and normal counterparts or in differently aggressive and invasive PCas [36,37,[52][53][54][55]. Overall, these studies strongly indicated Glo1 as a novel important protein involved in PCa genesis and progression, thus suggesting an oncogenic role for this enzyme in this neoplasm.…”
Section: Glo1mentioning
confidence: 95%
See 2 more Smart Citations